Space–time evolution of heavy sterile neutrinos in cascade decays - Daniel Boyanovsky (Nuclear Physics B, 2014)
Heavy sterile-like neutrinos may be produced resonantly from the decay of pseudoscalar mesons and may decay into several different channels in a cascade Φ→Lανh; νh→X. In general these are rare events with displaced vertices. We provide a non-perturbative and manifestly unitary framework that describes the cascade decay and yields the space–time evolution of the probabilities for sterile neutrinos, final states and the total number of events at a far detector. The results are general, valid for Dirac or Majorana neutrinos and only input the total decay rates and branching ratios for the production and decay channels. We apply the results to two examples of “visible” decay: (i) K+→e+νh→(e+)e+e−νe via a standard model charged current vertex and (ii) the radiative decay K+→μ+νh→(μ+)νaγ. For this latter cascade process we find substantial corrections to previous assessments within the parameter space argued to solve the anomalous excess of electron-like events at MiniBooNE.